First in the morning : 365 uplifting moments to start the day consciously - Osho. (New Delhi : Full Circle, 2014)
MIND, BODY, SPIRIT: MEDITATION & VISUALISATION. While many of us might start our day with emails and news, we can easily agree that this is not be the most inspirational start of a day. First in the Morning by Osho gives you a different option to start your day in a more meditative way, to give your mind a taste of meditation that carries you through the day. Here readers find short text pieces for daily meditations and inspiration to start the day. Simply start each day by reading a suggested passage for that morning. The extracts in this book, along with its companion volume, Last in the Evening, are selected from intimate one-on-one talks with Osho. This book, with passages specially selected for the morning, is invaluable for those already familiar with meditation, as well as the newcomer to the world of the inner mind.
Keywords: Meditation; Meditations